Cancellation Of Marriage Between Cinderela And Prince Based On Law Number 1 Year 1974 On Marriage - Ahdiat, Mulki; Purwaningsih, Prihatini; Iskandar, Dadang (Universitas Ibn Khaldun Bogor, 2023)
Nowadays, marriage is not only in the form of traditional ceremonies of belief or religion, but administrative recording is also needed for administrative purposes. Article 2 paragraph 2 of Government Regulation No. 9 of 1975 concerning the Implementation of Law No. 1 of 1974 concerning Marriage states that the registration of marriages of those who solemnise their marriages according to their religions and beliefs other than Islam, is carried out by the Marriage Registrar at the Civil Registry Office. This means that the Population and Civil Registry Office is tasked with recording and examining the truth of the occurrence of a person's marriage from certain religious leaders. But what if the Population and Civil Registry Office in carrying out its duties has been mistaken or at least the Population and Civil Registry Office did not verify the Prince's marriage report correctly. If it is related to the case of cancellation of marriage between Cinderela and Cinderela, it is due to the unprofessionalism of the Population and Civil Registry Office in the DKI Jakarta jurisdiction. Because the Department of Population and Civil Registry in the jurisdiction of DKI Jakarta has issued a marriage validation letter on behalf of Prince and Cinderela dated 8 January 2014, it is null and void, because the evidence base of the validation letter is a marriage blessing letter from the True Jesus Church on Jalan Samahudi, Central Jakarta, which states that Prince and Cinderela have undergone a blessing on 11 December 2013, which is declared fictitious or invalid. Thus, juridically, the marriage on behalf of Prince and Cinderela is declared invalid and deemed never to have occurred, but the decision to cancel the marriage does not apply retroactively to Prince's children with Cinderela.